2019
DOI: 10.1155/2019/9641860
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Sweeteners and Sugar Ingredients as Reducing Agent for Green Synthesis of Silver Nanoparticles

Abstract: An environmentally friendly technique has been developed to produce metal nanoparticles using green synthesis methods. In this study, silver nanostructures were synthesized using different sugar substitutes and artificial sweeteners as green reducing agents in an aqueous solution at low temperature. The main ingredients (such as maltodextrin, sucrose, saccharin, and sucralose) of the artificial sweeteners acting as reducing agents were used to reduce Ag+ ions to Ag0. The pH of the solution was controlled durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 59 publications
1
21
0
2
Order By: Relevance
“…In their study, AgNWs with diameters ranging from 10 to 20 nm and lengths of several hundreds of micrometers were obtained when isopropanol was used as the solvent, and AgNRs structures were obtained with a thickness of 100 to 200 nm and lengths of tens of micrometers when acetone and acetonitrile were used as the solvent. Hemmati et al obtained AgNRs using brown sugar as both reducing and capping agent [ 199 ]. The AgNRs were around 50 nm thick in diameter and a few micrometers long.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In their study, AgNWs with diameters ranging from 10 to 20 nm and lengths of several hundreds of micrometers were obtained when isopropanol was used as the solvent, and AgNRs structures were obtained with a thickness of 100 to 200 nm and lengths of tens of micrometers when acetone and acetonitrile were used as the solvent. Hemmati et al obtained AgNRs using brown sugar as both reducing and capping agent [ 199 ]. The AgNRs were around 50 nm thick in diameter and a few micrometers long.…”
Section: Reviewmentioning
confidence: 99%
“…Many green reagents can act as reducing and capping/stabilizing agent at the same time. However, this depends on the reaction mechanism and molecular structure of the reagent and its ingredients including particular functional groups such as amines, aldehydes, and carboxylates, to name a few [ 199 ]. Understanding the reaction mechanism is essential to tune and control the size and morphology-dependent properties of silver nanostructures.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemmati et al recently showed that Maui Raw Turbinado brown sugar acts simultaneously as a reducing and capping agent in synthesis of 1D silver nanostructures at low temperature (25-50°C) [159].…”
Section: Lessons From Polyol Agnw Synthesis Toward Green and Sustainamentioning
confidence: 99%